Development of a model for the detection, prevention and treatment of child abuse from the school system - Larraín H., Soledad; Sepúlveda, Gabriela (Revista de Psicología, 1999)
This paper proposes an interdiciplinary modes of detection, evaluation, prevention and treatment of children with evidence or suspect of abuse, and their family group, through the school system. It was designes an instrument to detect child abuse, to be applied by teacher and/or counselors. There were developed and applied Workshops, from a cognitive approach, for children, parents and teachers. the psychological evaluation of affective and social development of children suspect of abuse, shows a predominance of negative images of self and of the world, unsatisfactory interpersonal relationships, low level of both moral development and interpersonal problem solving. It is concluded that following the steps established in the proposed model, possible to develop a prventive program of child abuse in the community, starting from the school system, in which the teachers, previously trained, have a leadership role in the work with children and parents.